PENGARUH TEKNOLOGI DAN GOOD CORPORATE GOVERNANCE TERHADAP EFISIENSI PENGELOLAAN ZAKAT DI PROVINSI ACEH - Nahri, Arifin; Mutia, Evi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This research investigates how technology and Good Corporate Governance (GCG) impact the efficiency of zakat management in Aceh Province. GCG is measured through factors like board size and the presence of professionals on the board. Using a quantitative approach, this study analyzed secondary data from the Baitul Mal Directory, accessible via the Baitul Mal Aceh website, for the period 2016 to 2020. A convenience sampling method was adopted for sample selection, and multiple linear regression analysis was applied to assess the data. The findings show that board size, technology, and the expertise of board professionals all have a significant effect on zakat management efficiency. This suggests that optimizing governance structures and leveraging technology could enhance the efficiency of zakat management processes. The study offers valuable insights for policymakers and zakat institutions, especially in regions similar to Aceh, by highlighting the importance of governance and technology in increasing the accountability and effectiveness of zakat distribution.